1992
DOI: 10.1021/bi00123a032
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotope aided nuclear magnetic resonance study to investigate the receptor-binding site of human interleukin 1.beta.

Abstract: Resonance assignments for interleukin 1 beta at neutral pH were made by using three-dimensional NMR in combination with specific labeling and double-labeling methods with stable isotopes. On the basis of the present assignments, 15N single-quantum coherence spectra of N-terminal truncated and fusion mutants were compared with that of the wild-type. Although these mutants have reduced biological activity, they showed 15N-SQC spectra similar to that of the wild-type. However, small but significant chemical shift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…As illustrated in Figure 6, Gln12 and the N‐terminal segment are located in the vicinity of the 50th and 90th regions and may also be affected by the ANS binding. This view is supported by an earlier NMR study that showed that truncation of N‐terminal residues of structurally similar IL‐1β results in chemical shift perturbations localized to residues 41–47 and 86–99 (Tate et al 1992). Based on the structural alignment of IL‐1ra and IL‐1β, these positions correspond to the residues 47–52 and 85–99 of IL‐1ra (Schreuder et al 1995) and correlate well with the 50th and 90th regions.…”
Section: Resultsmentioning
confidence: 62%
“…As illustrated in Figure 6, Gln12 and the N‐terminal segment are located in the vicinity of the 50th and 90th regions and may also be affected by the ANS binding. This view is supported by an earlier NMR study that showed that truncation of N‐terminal residues of structurally similar IL‐1β results in chemical shift perturbations localized to residues 41–47 and 86–99 (Tate et al 1992). Based on the structural alignment of IL‐1ra and IL‐1β, these positions correspond to the residues 47–52 and 85–99 of IL‐1ra (Schreuder et al 1995) and correlate well with the 50th and 90th regions.…”
Section: Resultsmentioning
confidence: 62%
“…On the other hand, obtaining exhaustive amino acid type information entails preparation of up to 19 NMR samples, if the protein of interest contains all non-proline amino acid types. Sequence-specific amide group assignments are directly accessible via dual-selective labeling with 15 N and carbonyl (1-13 C) labeled amino acids, pioneered by Kainosho and Tsuji (1982) which has been demonstrated to be extremely useful for monitoring individual sites by measuring HNCOtype spectra (Gossert et al 2011;Griffey et al 1986;Rule et al 1993;Tate et al 1992;Weigelt et al 2002;Yabuki et al 1998). Aiming at full backbone assignments, separate samples with different pairs of amino acids would have to be prepared, and data to be collected on, to an extent of the same order of magnitude as the number of residues present in the protein, which is clearly unfeasible.…”
Section: Merits Of Combinatorial Selective Labelingmentioning
confidence: 99%
“…In a different approach, selective 15 N Electronic supplementary material The online version of this article (doi:10.1007/s10858-015-9941-8) contains supplementary material, which is available to authorized users. labeling provides amino-acid type information (Griffey et al 1985;Klammt et al 2004;LeMaster and Richards 1985;Muchmore et al 1989;Ozawa et al 2004Ozawa et al , 2006 while dual selective labeling with 15 N and 13 C isotopes additionally permits an identification of specific amino acid pairs via the interresidue 15 N i -13 C 0 iÀ1 scalar coupling (Griffey et al 1986;Ikura et al 1990b; Kainosho and Tsuji 1982;Rule et al 1993;Shi et al 2004;Tate et al 1992;Weigelt et al 2002;Yabuki et al 1998). NMR methods that rely on amino-acid specific isotope labeling usually feature decreased susceptibility to the adverse effects of slow molecular tumbling and conformational exchange.…”
Section: Introductionmentioning
confidence: 99%
“…Site‐specific information can be obtained with the help of dual selective labeling schemes, originally introduced by Kainosho and co‐workers . These methods use a combination of 15 N and 13 C labeling to identify unique amino acid pairs in the protein based on information either from J splittings in the 15 N dimensions of HMQC/HSQC spectra or from correlations observed in HNCO experiments . The application of single or dual selective labeling to investigate ligand binding can include the use of few labeled amino acids as “probes” in different subpockets of the target protein.…”
Section: Introductionmentioning
confidence: 99%